The Influence of The Work Environment, Compensation, and Motivation on Personnel Performance - Lestari, Rikka Indah; Krisnandi, Herry; Digdowiseiso, Kumba (International Journal of Social Service and Research, 2024)
The study aims to determine how much the influence of the work environment, compensation, and motivation on the personnel performance at Biro SDM Polda Metro Jaya. The population of this study is all personnel of the Biro SDM Polda Metro Jaya with a total of 155 personnel. The sample was taken using the simple random sampling technique with a total sample of 112 respondents. In this study using primary data in the form of questionnaires that have been distributed to 155 respondets. The results of this research were processed and analyzed with multiple linear regression analysis through the SPSS Version 22 program. The results of this study show that the work environment, compensation, and motivation at the HR Bureau Polda Metro jaya together have a positive and significant effect on personnel performance. The results of this study hope that the instasis can improve the work environment, compensation, and motivation can support personnel performance.